2021
DOI: 10.1177/14782103211021937
|View full text |Cite
|
Sign up to set email alerts
|

Response of educational institutions to COVID-19 pandemic: An inter-country comparison

Abstract: The ongoing global COVID-19 pandemic has revolutionized the education system and forced fundamental changes in the teaching–learning process. The present study aims to explore various modes of education used by educational institutions across the world and provide a holistic understanding of different measures taken by governments and universities to endure the crippling crisis. The radical shift to digital pedagogy followed by online assessments and examinations brought new experiences to both educators and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 62 publications
(137 reference statements)
5
47
0
1
Order By: Relevance
“…Anecdotally, just providing online resources and hoping that students will engage with them is not enough -without direction of their online activities, students are not engaging with the materials, resulting in a low level of academic understanding and limited active learning. Online teaching content and activities should therefore be more carefully considered since they require a completely different pedagogic approach to face-to-face teaching (Babbar & Gupta, 2021;Orlov et al, 2021;Pandya et al, 2021). In addition, the motivations, wellbeing and online engagement patterns of students need to be much better understood, and mechanisms put in place to support student learning more effectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anecdotally, just providing online resources and hoping that students will engage with them is not enough -without direction of their online activities, students are not engaging with the materials, resulting in a low level of academic understanding and limited active learning. Online teaching content and activities should therefore be more carefully considered since they require a completely different pedagogic approach to face-to-face teaching (Babbar & Gupta, 2021;Orlov et al, 2021;Pandya et al, 2021). In addition, the motivations, wellbeing and online engagement patterns of students need to be much better understood, and mechanisms put in place to support student learning more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has, since societal impacts started being felt around March 2020, necessitated significant and very rapid shifts in the nature, style and mode of engagement in teaching practices globally, at all levels and in all contexts (Ferri et al, 2020;Babbar & Gupta, 2021). The nature of transmission of the COVID-19 virus meant that face-toface teaching and in environments such as classrooms where social distancing could not be observed could no longer take place.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, virtual laboratories, where available, provided a salutary, even though not complete, replacement of physical laboratories. The rapid implementation in the current teaching process was marked by several challenges [11,12,14] (need for urgent curricula re-design, insufficient infrastructure, and training for the use of online tools, both for teachers and students, cyber security issues, harmful effects of prolonged exposure to electronic devices, etc. ), but also revealed numerous opportunities that were overlooked before.…”
Section: Introductionmentioning
confidence: 99%
“…They allow collaboration in groups to conduct experiments [75], while avoiding, at the same time, the health risks. The COVID-19 pandemic not only increased substantially the degree of implementation and use of VLs in educational institutions but also significantly improved the perception of the teaching staff about their utility [11,12,14,32,67]. Several authors consider that virtual laboratories will continue to be a constant presence in the post-COVID educational landscape, coexisting with physical laboratories [12,67,76].…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 8 Challenges as poor internet access, laptop shortages, difficulty in understanding digital admission processes, lack of self-motivation to study were observed across countries. 9 In this context, screen-time activities increased due to online schooling, online socializing and limited non-screen-based activities, physical exercise and social interactions were very abundant. 8 Data from the Health Behavior in School-aged Children study, in Czech Republic, showed that about one third of the students reported economic and psychosocial disruptions to their family life during lockdown, but that 79% also indicated that they had positive opportunities for family interactions or learning new contents.…”
Section: Introductionmentioning
confidence: 99%